Engaging hard-to-reach patients in patient-centered outcomes research. (May 2013) - Kauffman, Karen S; dosReis, Susan; Ross, Melissa; Barnet, Beth; Onukwugha, Eberechukwu; Mullins, C Daniel
Aims: This study aimed to identify methods to engage hard-to-reach patients in the research process.Materials & methods: With funding from the Patient-Centered Outcomes Research Institute (Washington, DC, USA), the University of Maryland (MD, USA) conducted 20 focus groups and one individual interview. The sample consisted of six groups of hard-to-reach patients, two groups of healthcare providers who work with hard-to-reach patients and two groups of surrogates of hard-to-reach patients.Results & conclusion: In order to make patient-centered outcomes research more meaningful to patients and their caregivers, patient-centered outcomes research should be conducted with a focus on building and maintaining trust, which is achieved via pre-engagement with communities and continuous engagement of study participants and their communities.